Criminal Justice Policy and Victim-Survivor Empowerment: A Case Study of Domestic Violence Disclosure Schemes in England and Wales - Barlow, Charlotte; Walklate, Sandra; Renehan, Nicole (feminists@law, 2024)
Empowering victim-survivors has long been recognised as one key strategy in reducing domestic abuse. This article explores whether Domestic Violence Disclosure Schemes as a criminal justice response to preventing domestic abuse in the United Kingdom are experienced as empowering in practice. Centralising victim-survivor voices, this article argues that variability in experiences of feeling empowered or disempowered pivoted upon whether those who deliver the scheme adopted an incident or process focussed approach. It concludes that while such schemes can be empowering when concomitant support is forthcoming, ultimately the victim-survivors in this study were left feeling disillusioned because of the disparities between what was expected and the limits of what was delivered in practice.